Literature Review: IT Management and Information Systems Analysis Using COBIT 5 - Nur Azizah Yusuf; Andi Hutami Endang (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
This study is a literature review that examines how the COBIT 5 framework is used to assess information technology (IT) management and information systems across various businesses. The study examined 100 scholarly papers to determine how COBIT 5 domains (EDM, APO, BAI, DSS, MEA) are distributed, what combinations of domains are used, what each study aims to assess, and how well IT processes are implemented. The study results indicate that the DSS and APO domains are the most commonly used. This is due to their strong focus on IT service operations and strategic planning. Furthermore, many studies integrate two to five areas to obtain more comprehensive evaluation results. These studies examine several aspects during the evaluation, such as process capability, strategic alignment, risk management, and information systems development. However, most studies indicate that IT process capability remains at levels 1 to 3. This study can serve as a foundation for organizations and researchers to design IT management improvement strategies that are more focused and aligned with organizational goals.